The Effect of Social Media on Company Marketing in Batam City - Ramadilla, Sephia (Terbuka Journal of Economics and Business, 2022)
This study aims to determine the influence of marketing that occurs on social media. And to find out the differences in marketing a product using offline and online systems. This study uses qualitative research methods, in-depth interviews, and observations of the influence of marketing and social media use. The subjects in this study are the public, this study concludes that producers need to utilize social media optimally and consistently in updating the information every day to develop and improve products or services on the market